Utility and Ethics of the Interrogation Method in a Virtual Environment - Mairena Quiñonez, Liyei M.; Murcia-Gutiérrez, Epimenio (Scientific journal of social studies, 2023)
Interrogation is a key method for a legal system that seeks to protect the ideals of justice and truth but, due to the implementation of virtuality, questions the utility and ethics of the medium in which it is executed, reconsidering accelerated changes in the law. both practical and theoretical. The cross-examination method of interrogations in obtaining credible testimonies is questioned, due to its techniques questioned by the psychology of testimony. Therefore, in the following work, through a deductive-analytical method with a qualitative methodology, it will be examined if the interrogation method is convenient, and if it responds to the demands of the efficiency of a digital environment.
Keywords: Ethics; interrogation; utility; psychology of testimony; virtuality